Play Cognitive Behavioral Therapy Improves The Concentration Of Children With ADHD - Kasiati; Sary Rina Naruvita; Umi Harti; Yulia; Septiyani Endang Yunitasari (Jurnal Scientia, 2022)
ADHD (attention deficit/hyperactivity disorder) or GPPH (attention deficit/hyperactivity disorder) is a neurodevelopmental disorder. ADHD is the medical term for a mental disorder characterized by impulsive and hyperactive behavior. This disorder affects children and they find it difficult to concentrate on one thing at a time. ADHD can have a serious impact on certain areas, such as studying or working. A therapist can help address areas that need special attention to provide strategies. One of the approaches used is cognitive behavioral therapy (CBT), this type of psychotherapy helps children change negative thought patterns into positive and healthier ways of thinking. The research subjects were children who were indicated to have ADHD. Data collection method is observation. The results of the study show that cognitive behavioral therapy can improve the concentration of children with ADHD.